Beyond Digital Buzz: Brand Image Shapes Purchase Intention from TikTok Usage, eWOM, and Green Marketing - Widi Senalasari; Revina Az-Zahra Pratiwi; Rafiati Kania (Politeknik Negeri Bandung, 2026)
The rapid growth of café businesses in Bandung, along with the increasing dominance of social media in shaping consumer decision-making, reflects a highly competitive and digitally driven market environment where firms must continuously adapt their strategies to remain relevant. In this context, younger consumers, particularly Generation Y and Z, increasingly rely on TikTok usage, electronic word-of-mouth (eWOM), and green marketing cues when evaluating brands, making brand image a crucial factor in shaping purchase intention. This study examines the mediating role of brand image in the relationship between TikTok usage, eWOM, green marketing, and purchase intention in Bandung’s café industry. Using a quantitative approach, data were collected from 433 respondents and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that TikTok usage, eWOM, and green marketing do not have significant direct effects on purchase intention. However, all three variables significantly influence purchase intention indirectly through brand image, indicating a full mediating effect. Furthermore, TikTok usage, eWOM, and green marketing significantly enhance brand image, which in turn strongly drives purchase intention, highlighting its critical role in translating digital engagement into consumer behavior.